GC-MS analysis of metabolites in tritrophic interaction of yeast (Pichia Kudriavzevii)against soft rot pathogen of carrot (Daucus carota) - S LAVANYA; P MUTHULAKSHMI; I JOHNSON (The Indian Journal of Agricultural Sciences)
Carrot a fleshy edible root vegetable, abundant in bioactive compounds such as carotenoids and dietary fibres. The market value of carrots is impacted by post-harvest illnesses, which have emerged as a serious production constraint. A promising advancement in the battle against post-harvest illnes is yeast-based biocontrol, because of its colonization on dry surfaces for longer periods and low nutrient utilization and can multiply easily. A study was carried out during 2022–23 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to evaluate the GC- MS analysis of metabolites in tritrophic interaction of yeast (Pichia Kudriavzevii) against soft rot pathogen of carrot. The tritrophic interaction of soft rot pathogen Pectobacterium carotovorum subsp. carotovorum and yeast isolate YKP 12 Pichia kudriavzevii was analyzed through GCMS analysis and the metabolite 1-Hexanol, 2-ethyl showed highest peak area of 13.89% with the retention time of 4.89 min. The tri-trophic interaction results revealed that the compound 1, 2-Benzenedicarboxylic acid monoester had both antibacterial and antifungal activity.